سوق اهراسANADالمؤسسات الناشئة في تحقيق التنمية المستدامة دراسة حالة الوكالة الوطنية لدعم وتنمية المقاولاتية - رحمة راجدي; ريان شهرزاد رزقي (My University, 2021)
This study dealt with the role of emerging institutions in the development of sustainable development, as it has become an important sector in the national economy due to its effectiveness, flexibility and ease of adaptation that make it able to contribute to the promotion of the economy. In addition to the environmental and technological aspect, as for the practical aspect, we have adopted the questionnaire as a methodological tool for the study in the social sciences, and then processing and analyzing the data collected on us and conducting statistical tests. Finally, on the basis of the findings, the study demonstrated the existence of an intermediate relationship between emerging enterprises and sustainable development, and finding an impact for emerging enterprises on achieving sustainable development ............................................................... تناولت هذه الدراسة دور المؤسسات الناشئة في تطوير التنمية المستدامة، حيث أصبح قطاعا هاما في الاقتصاد الوطني نظرا لفعاليتها ومرونتها وسهولة تكيفها التي تجعلها ا قادرة على المساهمة في ترقية الاقتصاد ففي الجانب النظري تم التطرق إلى دور المؤسسات الناشئة في تطوير التنمية المستدامة من الجانب الاقتصادي، والاجتماعي إضافة إلى الجانب البيئي والتكنولوجي، أما في الجانب التطبيقي فقد اعتمدنا الاستبياف كأداة منهجية الدراسة في العلوم الاجتماعية وبعد ذلك متابعة وتحليل المعطيات المحصل عليها وإجراء الاختبارات الإحصائية. وفي الأخير للدراسة وعلى أساس النتائج المتوصل إليها، أثبتت دراسة وجود علاقة متوسطة بين المؤسسات الناشئة والتنمية المستدامة وبهد أثر للمؤسسات الناشئة على برقيق التنمية المستدامة .